Investigation of the Antimicrobial Effect of Different Disinfectants on Alginate Measurement Materials - Güntekin, Neslihan; Arslan, Gökçe Kader; Özdemir, Mehmet; Tunçdemir, Ali Rıza (Journal of Pediatric Infectious Diseases, 2022)
Objective The impression materials are contaminated with pathogenic microorganisms carried by saliva and blood in the mouth. The aim of this study is to evaluate the antimicrobial activity of 1 and 5.25% sodium hypochlorite (NaClO) and zeta 7 solution, a commercial disinfectant, on alginate and to compare it washing with distilled water.Methods Samples obtained from alginate impressions taken from eight pediatric patients selected in accordance with the inclusion criteria with a size of 1 × 1 cm were subjected to five different disinfection protocols. After samples were vortexed in 3-mL physiological saline, 1-mL volume were inoculated onto brain heart infusion agar and cultured at 37°C for 72 hours to determine the number of colony-forming units/mL. Streptococcus mutans, Staphylococcus aureus, Escherichia coli, Candida albicans were used as control strains. The data obtained were statistically evaluated by using analysis of variance and post-hoc tests. The differences were considered statistically significant when p < 0.05.Results All of the disinfectant solutions tested were effective in the disinfection of the impression materials examined. The control group with no treatment and the water and flushing group had a significantly higher bacterial load compared to the other disinfectant-treated groups in terms of bacterial load, and no significant difference has been observed between the disinfectant solutions (p < 0.05). Simple rinsing of the impressions in sterile water reduced the number of microorganisms but did not decontaminate the impressions.Conclusion Washing with water alone is insufficient for measured disinfection. Although NaClO is an effective disinfectant even at low concentrations, microorganism growth was not observed at 5.25% concentration. It is appropriate to use NaClO at 1 and 5.25% concentrations for impression disinfection.
Keywords: antimicrobial effects; dental impression; disinfection; irreversible hydrocolloids; sodium hypochlorite